ERK2-dependent reactivation of Akt mediates the limited response of tumor cells with constitutive K-RAS activity to PI3K inhibition - Toulany, Mahmoud (Landes Bioscience, 2014)
K-RAS mutated (K-RASmut) non-small cell lung cancer (NSCLC) cells are resistant to EGFR targeting strategies. We investigated the impact of K-RAS activity irrespective of mutational status in the EGFR-independent increase in clonogenic cell survival. An analysis of the K-RAS activity status revealed a constitutively high K-RAS activity in K-RASmut NSCLC cells and also in head and neck squamous cell carcinoma (HNSCC) cells overexpressing wild-type K-RAS (K-RASwt). Similar to K-RAS-mutated cells, increased K-RAS activity in HNSCC cells overexpressing K-RASwt was associated with the stimulated production of the EGFR ligand amphiregulin and resistance to EGFR tyrosine kinase (EGFR-TK) inhibitors such as erlotinib. Expression of mutated K-RAS stimulated Akt phosphorylation and increased plating efficiency. Conversely, knockdown of K-RAS in K-RASmut NSCLC cells and in HNSCC cells presenting overexpression of K-RASwt resulted in sensitization to the anti-clonogenic activity of erlotinib. K-RAS activity results in EGFR-dependent and EGFR-independent Akt activity. The short-term treatment (2 h) of cells with EGFR-TK or PI3K inhibitors (erlotinib and PI-103) resulted in the repression of Akt activation, whereas long-term treatment (24 h) with inhibitors led to the reactivation of Akt and improved clonogenicity. The Akt re-activation was MAPK-ERK2-dependent and associated with a lack of complete response to anti-clonogenic activity of PI-103. A complete response was observed when PI-103 was combined with MEK inhibitor PD98059. Together, clonogenicity inhibition in tumor cells presenting constitutive K-RAS activity independent of K-RAS mutational status can be achieved by targeting of EGFR downstream pathways, i.e., PI3K alone or the combination of PI3K and MAPK inhibitors.